Copper(ii) thiosemicarbazone complexes induce marked ROS accumulation and promote nrf2-mediated antioxidant response in highly resistant breast cancer cells. Issue 12 (8th March 2017) - Sîrbu, Angela; Palamarciuc, Oleg; Babak, Maria V.; Lim, Jia Min; Ohui, Kateryna; Enyedy, Eva A.; Shova, Sergiu; Darvasiová, Denisa; Rapta, Peter; Ang, Wee Han; Arion, Vladimir B.
Abstract : The synthesis, characterisation and mode of action of water-soluble copper(ii )–TSC complexes are reported. Abstract : A series of water-soluble sodium salts of 3-formyl-4-hydroxybenzenesulfonic acid thiosemicarbazones (or sodium 5-sulfonate-salicylaldehyde thiosemicarbazones) containing different substituents at the terminal nitrogen atom (H, Me, Et, Ph) and their copper(ii ) complexes have been prepared and characterised by elemental analysis, spectroscopic techniques (IR, UV-vis, 1 H NMR), ESI mass spectrometry, X-ray crystallography and cyclic voltammetry. The proligands and their copper(ii ) complexes exhibit moderate water solubility and good stability in aqueous environment, determined by investigating their proton dissociation and complex formation equilibria. The copper(ii ) complexes showed moderate anticancer activity in established human cancer cell lines, while the proligands were devoid of cytotoxicity. The anticancer activity of the copper(ii ) complexes correlates with their ability to induce ROS accumulation in cells, consistent with their redox potentials within the biological window, triggering the activation of antioxidation defense mechanisms in response to the ROS insult. These studies pave the way for the investigation of ROS-inducing copper(ii ) complexes as prospective antiproliferative agents in cancer chemotherapy.